Beyond vulnerability: contextualizing migrant worker views on rights and wellbeing in the Gulf Arab states - Michael Ewers; Abdoulaye Diop; Nathan Duma; Kien Le (Comparative Migration Studies, 2023)
Abstract This paper examines migrant workers’ subjective views of their rights and wellbeing in the Gulf Arab state of Qatar. Since the announcement of the World Cup, Qatar has been roundly criticized for the living and working conditions of the low-wage migrant workers responsible for building the country’s social and economic infrastructure. These critiques, however, either emphasize individual migrant experiences of mistreatment or the kafala migration regime that regulates migration and employment. Few quantitative and representative studies ask migrants how they understand and experience their rights and wellbeing, or how these views have changed as the country has embarked on key labor law reforms in response to international pressure. Therefore, we present results from a large-scale, nationally representative survey of low-wage migrant workers conducted in labor accommodations over four years, supplemented by a separate phone survey. The analysis emphasizes the views of migrants—including satisfaction with rights, awareness of rights, fulfillment of contracts, and quality of life—which are critical to successful policy implementation. We examine the objective factors that best explain these views and study the interaction between subjective and objective wellbeing dimensions. The results inform scholarly understandings of the living and working conditions of migrants and provide essential context for questions surrounding migrant rights and global justice in temporary labor migration regimes.